Efektivitas Pelaksanaan Restorative Justice dalam Penyelesaian Kasus Tindak Pidana Penganiayaan di Kepolisian Resor Gorontalo Utara - Apriyansa Pranata Ayuba; Suwitno Yutye Imran; Julisa Aprilia Kaluku; Dolot Alhasni Bakung (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This activity aims to determine whether the implementation of restorative justice is effective in resolving criminal cases of abuse in the North Gorontalo Resort Police and to find out what obstacle factors cause the implementation of restorative justice in the North Gorontalo Resort Police to be ineffective. The type of research used is legal research. empirical. The research results show that (1) the ineffectiveness of the implementation of restorative justice in resolving cases of criminal abuse at the North Gorontalo Police Department. (2) The limited number of investigators has an impact on performance in implementing restorative justice, apart from that, remote location is also an inhibiting factor because it takes time and money.